Structure and chemical ordering in amorphous silicon carbide alloys - Kelires, Pantelis C. (My University, 1991)
Simulations of amorphous silicon carbide alloys indicate that the amorphous network deviates from an ideal tetrahedral geometry due to the presence of threefold- coordinated carbon atoms. All samples exhibit a significant degree of chemical ordering, most of it arising from fourfold-coordinated carbon atoms. The results show that there is no phase separation and that hydrogenation might promote tetrahedral carbon coordination, as well as chemical ordering. © 1991 IOP Publishing Ltd.